Biostratigraphy of the Gurpi Formation in Chenareh section based on calcareous nannofossils - Zeinab Bayat; Anoshiravan Lotfali Kani; Jahanbakhsh Daneshian (Journal of Stratigraphy and Sedimentology Researches)
Abstract The Gurpi Formation was measured and sampled in a stratigraphic section located on the northern limb of the Chenareh anticline to the north of Andimeshk. The thickness of the Gurpi Formation in this section is 288.5 meters and its lower boundary with the Ilam Formation is abrupt while its upper boundary with purple shales of the Pabdeh Formation is gradual and continuous. Paleontological studies led to the identification of 67 species belonging to 45 genera from 20 families of calcareous nannofossils, which made it possible to recognize CC18 to CC26 biozones from Sissingh standard classification scheme and NP1 to NP5 biozones from Martini standard classification scheme equivalent to biozones CNP1 to CNP7 from Agnini et al.. Based on the identified biozones, the duration of deposition of the Gurpi Formation was determined to be early Campanian–Selandian. In this section, the Emam Hassan Limestone Member was recognized with a thickness of 112.8 meters having been deposited during the early Maastrichtian. Both the lower and the upper boundaries of the Emam Hassan Limestone Member within the Gurpi Formation are continuous and gradual. The position of the Campanian–Maastrichtian, Maastrichtian–Danian (Cretaceous–Paleogene) and Danian–Selandian transitions in the Gurpi Formation were also determined in the studied section. Keywords: Gurpi Formation, Chenareh anticline, Calcareous nannofossils, Cretaceous–Paleogene transition